Anthropology in an Era of Permanent War - Lutz, Catherine (Anthropologica, 2022)
Anthropologists are increasingly called on to work within and for military institutions in the United States. The entanglement of anthropological knowledge and military power should be set in context of the monumental growth and size and the imperial deployment of the U.S. military. There has been a striking absence of work in anthropology around the question of U.S. military power during the six decades of its permanent mobilization. This paper distinguishes between an anthropology of and an anthropology for the military, and proposes research foci that might help our discipline understand militarization, its effects and the routes to its reversal.